Combined finite-discrete element modellings of rockbursts in tunnelling under high in-situ stresses. (September 2021) - Han, Haoyu; Fukuda, Daisuke; Liu, Hongyuan; Fathi Salmi, Ebrahim; Sellers, Ewan; Liu, Tingjin; Chan, Andrew
Abstract: Rockburst is one of the severe geotechnical problems that may occur while tunnelling under high in-situ stresses. Despite numerous studies in the relevant literature, the evaluation and prediction of the rockburst still remain a common challenge worldwide. In this paper, a self-developed combined finite-discrete element method (FDEM) is used to numerically investigate the rockbursts in deep tunnelling under high in-situ stresses. The rockbursts in the drainage tunnel at the Jinping II Hydropower Station are modelled and the effects of the geological and geotechnical characteristics of the site on the occurrence of rockbursts are investigated. The FDEM numerical modelling vividly simulates the fracture initiation and propagation, as well as the fragment expulsion, ejection and flyout resulting in the rockburst process that could be difficult to capture on the site or via the conventional continuum modellings. The effect of the pre-existing fault on the site is studied, and the critical roles of the location and the dip angle of the fault in determining the rockburst development around the tunnel are highlighted. Then, the effects of in-situ stresses on rockburst development are investigated by applying different lateral pressure coefficients in the model. It is found that based on the Jinping site condition, a low lateral pressure coefficient could contribute to the alleviation of the rockburst around the tunnel but the alleviation effect is relatively limited, while a high lateral pressure coefficient could result in the rockburst that breaks more rock masses on the tunnel surface. Moreover, the influences of tunnel shapes on the rockburst incidents are also studied by further modelling rockbursts around tunnels in square shape and horseshoe shape. It is found that the square shape is inadequate in controlling rockbursts at the roof and floor areas, and the most suitable tunnel shape to resist rockbursts in such field condition is the circular shape. By vividly reproducing the rockburst processes in deep tunnelling under high in-situ stresses and elaborating the effects of several critical geological and geotechnical characteristics on the rockburst development around the tunnel, this study contributes to the understanding of the associated rockburst mechanisms and is also of guiding importance for certain tunnelling designs and constructions in practice. It is also expected that the proposed method can be used to evaluate and predict the rockbursts in many other scenarios in future studies.